Pulmonary Function, Aerobic Capacity and Related Variables in Patients With Ankylosing Spondylitis - Ayla ÇAĞLIYAN TÜRK,; Sertaç ARSLAN,; Yusuf KARAVELİOĞLU,; Macit KALCIK,; Sumru ÖZEL,; Ahmet MUSMUL,; Füsun ŞAHİN, (Archives of Rheumatology, 2019)
Objectives: This study aims to evaluate the cardiopulmonary functions and exercise performance of patients with ankylosing spondylitis (AS) and to investigate the relationship between these parameters and disease activity, spine mobility and quality of life (QoL). Patients and methods: Forty-five patients with AS (group 1; 33 males, 12 females; mean age 43.1±12.1 years; range 22 to 70 years) and 30 control subjects (group 2; 23 males, 7 females; mean age 42.8±10.0; range 23 to 70 years) were included in the study. Disease activity was assessed with the Bath Ankylosing Spondylitis Disease Activity Index and spinal mobility measures with the Bath Ankylosing Spondylitis Metrology Index (BASMI). The Ankylosing Spondylitis Quality of Life (ASQoL) Questionnaire and the Maastricht Ankylosing Spondylitis Enthesitis Score (MASES) were used. The pulmonary function test (PFT) and cardiopulmonary exercise testing (CPET) were performed. Results: There was no significant difference between groups 1 and 2 in terms of mean age. The peak expiratory flow value in PFT was significantly lower in group 1 (p<0.05). In group 1, the duration of CPET was significantly shorter, and maximum work load and metabolic equivalent were significantly lower than in group 2 (p<0.001). Maximum oxygen uptake (VO2max) in peak responses, work and heart rate were significantly lower in group 1. The duration of CPET and maximum work were negatively correlated with age and BASMI (p<0.001). VO2max was negatively correlated with age, MASES and ASQoL (p<0.05). Conclusion: There was no significant difference in PFT parameters between the groups. On the other hand, CPET parameters were significantly lower in the AS group. While CPET parameters are affected by spinal mobility, declining aerobic capacity affects QoL.